PARIWISATA SUNGAI KALIMAS SEBAGAI SALAH SATU DESTINASI PARIWISATA BERKELANJUTAN DI SURABAYA - Nugroho, Truli; Adinugroho, Suryo; Faskahariyanto, Kristian; Prakoso, Yusak; Mulyomo, Andreas Aris Eko (JURNAL LENTERA BISNIS, 2025)
The Kalimas River, located in the heart of Surabaya, is a crucial yet underexplored asset for sustainable tourism development. This study aims to explore the potential of the Kalimas River as a sustainable tourism destination, analyzing its role in supporting economic, social, and environmental sustainability in Surabaya. Using a mixed-methods approach, combining qualitative and quantitative research with 100 respondents, the study assessed tourist satisfaction, environmental impact, and local community engagement. The findings indicate that while the Kalimas River has significant potential to promote ecotourism, challenges remain related to infrastructure, environmental preservation, and stakeholder collaboration. This study highlights the importance of community-based tourism strategies and environmentally friendly practices in sustaining tourism growth along the river. The study's contribution lies in providing recommendations for policymakers and tourism stakeholders to enhance the role of the Kalimas River in Surabaya's tourism development while ensuring its sustainability for future generations.